Technology of Forming Roof Top Flowers: Basic Principles: Teknologi pembentukan atap berbentuk bunga: Prinsip Dasar - Karimov, Karimov (Indonesian Journal of Innovation Studies, 2024)
This scientific article rigorously investigates the formation of rooftop flowers, addressing key factors such as climate characteristics, construction requirements, rules, and drainage considerations. Employing a scientific and theoretical approach, the study delves into the technological aspects, including the filter layer and other relevant techniques. The goals encompass understanding the intricate relationship between rooftop vegetation and environmental factors. The research employs systematic methods to explore the theoretical underpinnings and practical implications of rooftop flower construction. Results highlight the significance of meticulous design, robust roof structures, efficient irrigation, suitable plant selection, and sustainable practices. The concluding remarks underscore the importance of these findings in enhancing both the aesthetic appeal and functionality of green rooftops, providing valuable insights for global researchers and practitioners in related fields. Highlights: Innovative Design: Meticulous design principles play a pivotal role in achieving visually appealing and environmentally beneficial rooftop flower formations. Climate-Responsive Construction: The study emphasizes the significance of constructing rooftop gardens resilient to diverse climatic conditions, ensuring long-term viability and adaptability. Effective Drainage Management: Successful implementation relies on optimized drainage systems, preventing water stagnation and safeguarding both the rooftop structure and the underlying environment. Keywords: Irrigation, Drainage, Rooftop Flowers, Green Roof Technology, Sustainable Urban Design